A multicentre study on the clinical characteristics of newborns infected with coronavirus disease 2019 during the omicron wave - Dai, Yi-Heng; Li, Caihuan; Yuan, Guilong; Mo, Wenhui; Chen, Jun; Huang, Runzhong; Wan, Zhonghe; Lin, Duohua; Zhong, Xiangming; Li, Huanqiong; Liu, Ling; Shi, Jipeng (Frontiers in Pediatrics, 2023)
A multicentre study on the clinical characteristics of newborns infected with coronavirus disease 2019 during the Omicron Wave 【Abstract】 Objective To investigate the clinical characteristics and outcomes of newborns infected with coronavirus disease 2019 (COVID-19) during the Omicron wave. Methods From December 1, 2022, to January 4, 2023, clinical data were collected from neonates with COVID-19 who were admitted to 10 hospitals in Foshan City, China. Their epidemiological histories, clinical manifestations and outcomes were analysed. The neonates were divided into symptomatic and asymptomatic groups. The t test or χ2 test was used for comparisons between groups.Results A total of 286 children were diagnosed, including 166 males, 120 females, 273 full-term infants and 13 premature infants. They were 5.5 (0-30) days old on average when they were admitted to the hospital. These children had contact with patients who tested positive for COVID-19 and were infected through horizontal transmission. This study included 33 asymptomatic and 253 symptomatic patients, among whom 143 were diagnosed with upper respiratory tract infections and 110 were diagnosed with pneumonia. There were no severe or critical patients. Fever (220 patients) was the most common clinical manifestation, with a duration of 1.1(1-6) days. The next most common clinical manifestations were cough with nasal congestion or runny nose (4 patients), cough (34 patients), poor appetite (7 patients), shortness of breath (15 patients), and poor general status (1 patient). There were no significant abnormalities in routine blood tests among the neonates infected with COVID-19 except for mononucleosis. However, compared with the asymptomatic group, in the symptomatic group, the leukocyte and neutrophil granulocyte counts were significantly decreased, and the monocyte count was significantly increased.C-reactive protein (CRP) levels were significantly increased (≥10 mg/L) in 9 patients. Myocardial enzyme, liver function, kidney function and other tests showed no obvious abnormalities. Conclusions In this study, neonates infected with the Omicron variant were asymptomatic or had mild disease. Symptomatic patients had lower leucocyte and neutrophil levels than asymptomatic patients.【Keywords】Neonates; coronavirus disease 2019; Omicron wave